Rancang Bangun Game Puzzle The Tabperi Dengan Algoritme A* Berbasis Android - Feni Melati; Aprianti Putri Sujana; Sri Nurhayati (Computer Engineering Departement, Universitas Komputer Indonesia, 2021)
Chemical elements are a subject in high school levels However, the abstract table of chemical elements often makes students lazy to memorize and remember a periodic table of chemical elements. To help students, one of them is by taking advantage of technological developments by making educational game applications in the form of 2- dimensional puzzle games. This application program is intended to help students hone their memory on the periodic table of chemical elements by arranging the randomized table arrangement into a complete table. Users can choose the level of play freely according to what they want. The program uses a-star algorithm and applies heuristic methods. The a-star algorithm can solve the problem optimally to find ... the shortest path to the goal. The application of the heuristic method is used to directly sort the results obtained without having to follow all paths. The test results show all the features and the implementation of the algorithm in this game application are running properly.